The application of actor-network theory to understanding social ecological systems related to human wildlife conflict: the issue of reintroducing gray wolves on the Western Slope of Colorado - Adamson, Claudia, author; Bright, Alan, advisor; Teel, Tara, advisor; Amidon, Tim, committee member; Niemiec, Rebecca, committee member (Colorado State University. Libraries, 2025)
The reintroduction of gray wolves (Canis lupus) to the Western Slope (WS) of Colorado was a mandated initiative outlined by the approval of Proposition 114 in November of 2020. Despite the approval by a majority of Colorado voters, the reintroduction of wolves has led to a multitude of conflicts, including social conflict and human-wildlife conflict (HWC) events. Researchers interested in understanding and addressing HWC rely on social science frameworks to evaluate the human factors that may affect the true or perceived severity of HWC events. Actor-network theory (ANT) has been used to describe social-ecological systems, including resilience and conflicts, in response to conservation initiatives. However, it has never been used as a framework to describe HWC systems. Through the collection and analysis of 58 digital artifacts, we developed a cohesive account of the social-ecological system (SES) of the WS in three key periods: (1) Ballot Creation and Approval (2018 - November 2020), (2) Preparation and Implementation of Reintroduction (November 2020 – December 18, 2023), and (3) Post Reintroduction (December 18, 2023 – May 2025). From these case studies, we created actor-network (AN) diagrams to describe how relationships between human and non-human actors can inform the structure and function of an SES experiencing HWC. The novel application of ANT was found to be a potentially valuable tool for wildlife management agencies due to its ability to de-center the human and focus on the relationships between human and non-human actors to more effectively lead to the symbolic and material occurrences of HWC.
Keywords: human-wildlife conflict; social-ecological systems; actor-network theory; wolves; rhetoric